Development of Capcut-Based Learning Media in Pancasila Education Learning - Tul Asanah, Fadila; Rafhi Febryan Putera (Journal of Practice Learning and Educational Development, 2025)
This research is motivated by the lack of utilization and use of IT-based learning media in line with the times, as well as the lack of variety in available learning media. The purpose of this research is to develop capcut-based interactive media, where students will learn through media that has been validated and categorized as valid, practical, and effective. The type of research conducted is Research and Development (R&D) using the ADDIE model which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research data were obtained through a validation questionnaire filled out by material experts, linguists, and media experts, as well as a practicality questionnaire filled out by teachers and students. The trial subjects consisted of 28 fourth grade students of SDN 02 Aur Kuning, while the research subjects included 16 fourth grade students of SDN 10 Sapiran. The data analysis technique used is a Likert scale. The results of the analysis show the validation of learning media by experts, and the practicality of learning media is tested through teacher and learner response questionnaires. Data collection instruments include learning media validation instruments, learning media practicality instruments, and learning media effectiveness instruments. The results of the material validity test on the development of capcut-based interactive media show a percentage of 73%, which is included in the valid category. The language validity test obtained a result of 98%, also with a very valid category. For the media validity test, the result is 84% with a very valid category. Meanwhile, the results of the practicality test showed a percentage of 96% from the teacher response questionnaire and 94.91% from the student response questionnaire, both with a very practical category. The effectiveness test results obtained a percentage of 87%, which is included in the very effective category. Thus, it can be concluded that the use of capcut-based learning media in learning Pancasila Education grade IV in elementary schools is proven to be valid, practical, and effective in supporting the learning process.